A Sequential Approach to the Management of Ostial Coronary Lesions via the Modified Flower Petal Technique - Ermis, Emrah; Ucar, Hakan; Allahverdiyev, Samir; Yildirim, Erkan (International Journal of Angiology, 2020)
There is still no consensus on the optimal technique for performing percutaneous coronary intervention (PCI) in ostial coronary lesions, due to potential complications. The modified flower petal technique is one of the techniques to management of ostial lesions. It seems suitable technique in terms of covering the coronary ostium well. In this report, we discuss a patient who underwent PCI with sequential modified flower petal technique, first to the left anterior descending artery ostial lesion, and then to the circumflex artery (CXA) upon the ostium of CXA was affected after the procedure following coronary angiography.
Keywords: ostial coronary lesions; modified flower petal technique; percutaneous coronary intervention; new techniques; left main coronary artery